Transtorno do espectro autista e a dinâmica familiar - Graciano, Olenice Ernesto de Araújo (2023)
Autism spectrum disorder is a globalneurodevelopmental disorder that manifests early, characterized by deficits that impair reciprocal communication, social interaction, and by restricted and repetitive patterns of behaviors, interests, and activities, and whose diagnosis impacts the family context. Following this path, this study aimed to analyze the family dynamics after the diagnosis of autism spectrum disorder; More specifically, to know the daily challenges of the family in the care of these children and to understand the repercussion of the diagnosis of children with autism spectrum disorder on family dynamics. This is a descriptive and exploratory study, with a qualitative approach, carried out in Campina Grande, Paraíba, Brazil. The study participants were parents of children who had been diagnosed with autism spectrum disorder between 1 and 5 years and are followed up at the Child Psychosocial Care Center. Data collection was carried out based on the focus group technique consisting of 6 parents, guided by an interview script. The data resulting from the focus group were submitted to content analysis, thematic modality. The participants in this group had the following characteristics: aged between 33 and 42 years, predominantly female; the majority have completed high school; all with a monthly income of one minimum wage; self-declared Christians; the majority of mixed race/color; 50% of the group were single and 50% were married. The categorical analysis showed that the family's daily challenges in caring for children permeate the understanding of Autism Spectrum Disorder, due to weaknesses related to access to information, socialization/communication and the quality of assistance/treatment in health and education services. Furthermore, it was found that the psychosocial changes in the family dynamics of children with ASD constitute a reason for concern for families, due to difficulties related to stigma, the daily post-diagnosis routine within the family, the family support network, adequate management of the child with ASD in the family environment. Analysis of family dynamics, after diagnosis of ASD, shows that it is affected as a whole, given the accumulation of demand for care and the change in routine, both in the personal and professional aspects, as a result of exclusive dedication to the child. Further research is recommended to enrich discussions on the topic, and to strengthen Public Health Policies related to people with autism spectrum disorder and their families.